THE COMPARISON OF USING PQ4R AND SQ3R TECHNIQUE TOWARD THE STUDENTS’ READING COMPREHENSION IN ANALYTICAL EXPOSITION TEXT AT ELEVENTH GRADE OF SMA NEGERI 1 TRIMURJO ACADEMIC YEAR 2015/2016 - Gustianing, Defy; Puspita, Adellina Octa (JOURNAL OF ADVANCED ENGLISH STUDIES, 2021)
The objectives of this research are to know whether there is difference of students’ reading comprehension by using PQ4R and SQ3R techniques or not and to find out which one is more effective between PQ4R technique and SQ3R techniques. Kind of this research is a quantitative research. The design of this research is pre-test, post-test control group design, which employs two groups at SMA N 1 Trimurjo. Experimental group is treated by PQ4R technique and Control group by SQ3R technique. Then, the total population are 170 students and 40 students as the sample taken by cluster random sampling. Based on the data analysis, assuming equal test shows that trasio is 2,80 and ttab on 0.01% is 2,70, so µ1 ≠ µ2 ( There is difference result between PQ4R and SQ3R technique). Then by assuming unequal test gives result trasio 2,80 and ttab on 0.01% 2,70, it means trasio (2,80) > ttab (2,70), so µ1 > µ2 ( PQ4R technique is higher than SQ3R technique). From both of calculation, it can be concluded that PQ4R is more affective than SQ3R technique toward students’ reading comprehension in Annalytical Text at elevent grade of SMA N 1 Trimurjo academic year 2015/2016.